2020
DOI: 10.1088/1361-6560/ab58ad
|View full text |Cite
|
Sign up to set email alerts
|

A spectral reconstruction algorithm for two-plane Compton cameras

Abstract: One factor limiting the current applicability extent of hadron therapy is the lack of a reliable method for real time treatment monitoring. The use of Compton imaging systems as monitors requires the correct reconstruction of the distribution of prompt gamma productions during patient irradiation. In order to extract the maximum information from all the measurable events, we implemented a spectral reconstruction method that assigns to all events a probability of being either partial or total energy depositions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…three-interaction events which allow to determine the energy of the primary gamma [46]. Another approach, reported recently in [55], takes into account the probability of incomplete energy deposition of a primary gamma in the detector. The aspect of computation speed was addressed in [56], where it was shown that a fast line-cone reconstruction technique yields significantly lower precision than an iterative maximum likelihood expectation maximization algorithm.…”
Section: Compton Camera (Cc)mentioning
confidence: 99%
“…three-interaction events which allow to determine the energy of the primary gamma [46]. Another approach, reported recently in [55], takes into account the probability of incomplete energy deposition of a primary gamma in the detector. The aspect of computation speed was addressed in [56], where it was shown that a fast line-cone reconstruction technique yields significantly lower precision than an iterative maximum likelihood expectation maximization algorithm.…”
Section: Compton Camera (Cc)mentioning
confidence: 99%
“…There are several Compton camera studies that investigated the ARM [61], [62] and spatial resolution [63], [64] of 88 Y, which emits gamma rays of 898 keV, close to 909 keV. Although it is difficult to compare them quantitively because of differences in configuration and application of the measurement system, those papers reported the ARM value was about 4 • and the spatial resolution was about 4-5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…The expression in equation ( 3) is modified to include the factors relating the deposited energies with the different possible incident photon energies. After inclusion of these factors, as deduced in (Muñoz et al 2020), the calculation of the system matrix elements is given by the expression:…”
Section: Image Reconstructionmentioning
confidence: 99%
“…For each event, a row of the system matrix is constructed using four-dimensional (three spatial and one spectral) voxels, so that the reconstruction algorithm is able to find both the spatial distribution and the energy of emission of the measured sources. Spectral image reconstruction methods for Compton imaging devices have been previously developed as a means of reconstructing sources with an unknown emission spectrum or a continuous one (Xu & He 2007, Gillam et al 2011, Muñoz et al 2020. The model employed in this work follows the one presented in (Muñoz et al 2020), with several modifications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation